THE PHONOLOGICAL VARIATIONS IN BUGIS SPEECH AT JUNIOR HIGH SCHOOL STUDENTS IN BARRU DISTRICT - Yulika R; Warsidi Warsidi; Jusmaniar N (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2024)
The objective of this research is to find out the phonological variations of Buginese speakers MTSS Muhammadiyah Ele students when they speak Indonesian. The researcher used a qualitative descriptive approach with agih data collection methods. The agih method is data analysis that uses parts or elements of the language itself as a determining tool. In this research, the researcher chose subjects according to the needs and objectives of the research. The researcher researched all class VII.1 MTSS Muhammadiyah Ele students. The results showed that there were three aspects of phonological variation found in this study. Findings from the addition of phonemes pronounced by Bugis (BL) speakers, for example, the addition of the phoneme /ma/ at the beginning of the word (prothesis) in the word [cantik] to become /macanti/. The addition of the phoneme /g/ at the end of the word (paragoge) in the word [teman] changes to /temang/. The findings from changes in phonemes spoken by Bugis speakers are that the consonant phoneme /a/ becomes /e/, /o/ as in the word [iya] becomes /iye/ and /iyo/. The release of the phoneme in the word [banyak] becomes /banya/, apart from that there is a release of the diphthong phoneme (ai) and (au), for example, the word [pakai] changes to /pake/, and the word [kalau] changes to /kalo/. It can be concluded that Indonesian (IL) used by Bugis (BL) speakers at MTSS Muhammadiyah Ele Barru Regency, especially class VII students, has many variations of the language in everyday life.